2017
DOI: 10.1212/wnl.0000000000004519
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord perfusion pressure predicts neurologic recovery in acute spinal cord injury

Abstract: We demonstrate that maintaining SCPP above 50 mm Hg is a strong predictor of improved neurologic recovery following spinal cord injury. This suggests that SCPP (the difference between MAP and CSFP) can provide useful information to guide the hemodynamic management of patients with acute spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 18 publications
1
107
0
Order By: Relevance
“…; Squair et al . ). To investigate the severity of orthostatic intolerance in the present study, we conducted head‐up tilt testing both pre‐ and post‐SCI.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Squair et al . ). To investigate the severity of orthostatic intolerance in the present study, we conducted head‐up tilt testing both pre‐ and post‐SCI.…”
Section: Discussionmentioning
confidence: 97%
“…This is especially pertinent not only for the maintenance of appropriate haemodynamics but also because mean arterial pressure, along with changes in cerebrospinal fluid pressure (Squair et al . ), are known to influence spinal cord perfusion pressure and therefore neurological recovery (Hawryluk et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since clinical features do not accurately predict SCPP opt , invasive ISP monitoring remains the only way of determining SCPP opt . A recent study showed that SCPP can be calculated by monitoring CSF pressure using a lumbar catheter and that SCPP measured in this way better correlates with outcome than MAP [30]. Monitoring CSF pressure is less invasive than monitoring ISP.…”
Section: Discussionmentioning
confidence: 99%